The influence of inhomogeneities of materials on spectrometric characteristics of silicon detectors - Saymbetov, A.K.; Japashov, N.M.; Sissenov, N.K.; Mukhametkali, B.K.; Kuttybay, N.B.; Tulkibayuly, Ye.; Nurgaliyev, M.K.; Mansurova, A.A. (Recent Contributions to Physics, 2016)
This work deals with influence of inhomogeneities of initial materials, for manufacturing Si(Li) detectors, on detector’s spectrometric characteristics. It is shown the results of investigation of structural features of Si(Li) detectors. The results of the research, of diffusion and drift of lithium ions into silicon, grown by Chohralski method and floating zone melting method, were described. It was shown that insufficient compensation of detector’s sensitive area is due to existence of local inhomogeneities in initial crystal volume, and also with imperfection of contacts of p-i-n structure. Moreover, it was described the current- voltage and farad- voltage characteristics of Si(Li) detectors. Also, the energy spectra of detector structure on the β-particles 207Bi (Eβ = 1 MeV) Rβ = 38 keV and α-particles 226Ra (Eα = 7.65 MeV) Ra = 65 keV was illustrated. It was experimentally approved that the results from low ohm p-Si crystal, grown by Chohralski method, have advantages to manufacture of big size Si(Li) p-i-n detectors, with low value of reverse current and high exploitation characteristic.